Security System Analysis Using the HTTP Protocol Against Packet Sniffing Attacks - Manguling, Inez sri wahyuningsi; Parenreng, Jumadi Mabe (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
The security level of the SIM MBKM website information system needs to be analyzed because it is accessed by many students who provide essential data. The security testing process for the SIM MBKM system uses the software Ettercap and Wireshark to test the system's security level and network data against cybercrime attacks. The results of these experiments showed the same essential data, but Wireshark displayed more personal information. The difference lies in the system architecture using different methods or stages, namely ARP Poisoning and Filtering HTTP. The third difference is the estimated time taken during the experiment. Ettercap and Wireshark applications enable eavesdropping on confidential and essential data and information. Through security testing using Ettercap and Wireshark, more critical data is displayed. solutions and preventive actions can be implemented by encrypting confidential data and improving website security using the HTTPS (Hypertext Transfer Protocol Secure) protocol.